1981
DOI: 10.1104/pp.68.6.1257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnesium on Intact Chloroplasts

Abstract: MATERIALS AND METHODS Plant Growth and Chloroplast Isolation. Spinach (Spinacia oleracea L.) plants were grown in the greenhouse or growth chamber-grown (12-h photoperiod, 22°C day/170C night). Leaves were ground briefly in a Waring Blendor2 using an iced slurry containing 0.33 M sorbitol, 10 mm Na4P207 (pH 6.5), 5 mM MgC12, and 2 mm isoascorbate (12). The chloroplasts were pelleted by centrifugation at 2,000g for 5 s. Chloroplasts from greenhousegrown spinach were washed in a buffer containing 0.4 M sorbitol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 5 publications
4
53
3
Order By: Relevance
“…However, the relationship shown in Figure 10 (10) The experiments relating altered chloroplast envelopebound Mg24 with photosynthetic capacity (Figs. 9 and 10) extend some hypotheses developed by Huber (12,17) and Gimmler (8,11). These experiments support the contention that Mg24 bound to the chloroplast envelope, and not necessarily high external Mg2", may affect stromal pH and, hence, photosynthetic capacity.…”
Section: Photosynthesismentioning
confidence: 69%
See 3 more Smart Citations
“…However, the relationship shown in Figure 10 (10) The experiments relating altered chloroplast envelopebound Mg24 with photosynthetic capacity (Figs. 9 and 10) extend some hypotheses developed by Huber (12,17) and Gimmler (8,11). These experiments support the contention that Mg24 bound to the chloroplast envelope, and not necessarily high external Mg2", may affect stromal pH and, hence, photosynthetic capacity.…”
Section: Photosynthesismentioning
confidence: 69%
“…Previous research has indicated that incubation of chloroplasts in medium with several millimolar Mg2+ can result in H+ influx into the chloroplast resulting in stromal acidification and inhibition of photosynthesis (8,17). Mg2+ inhibition of photosynthesis is characterized by a class of effects typical of other treatments which result in stromal acidification.…”
Section: Photosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Maury et al (15) postulated a Mg2+-activated reversible K+/H+ exchange. In these studies, it was assumed without any direct measurement of Na+ flux that Na+ also behaved like K+.…”
Section: Discussionmentioning
confidence: 99%